MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA GAMBAR SISWA KELAS V SEKOLAH DASAR - Ani Suryani (Dharmas Education Journal (DE_Journal), 2021)
This research is motivated by the low interest in students' reading comprehension which is still below the KKM. The purpose of this study is to describe the improvement of students' reading comprehension skills by using picture media. This study uses a qualitative approach with classroom action research design. The research subjects were 29 students of class V SDN 266/VI Bukit Beringin. The design of this research includes the planning stage, the implementation stage, the observation stage and the reflection stage. The collection instruments were a) student activity observation sheets, b) interviews in the implementation of the lesson. The data analysis technique used percentage analysis. This increase can be seen from the average score obtained by students, namely in the first cycle the score is 65, this is below the KKM 70. Then in the second cycle there is an increase in the score obtained by the students, namely 74 with the KKM 70..